The impact of family business leader’s confidence in succession process - Mohd Shariff, Mohd Noor; Salim, Linda; Ahmad Arshad, Darwina (2017)
Part of what makes family business is the intention of leaders to pass the business to the next generation. At the same time, there is a sobering fact that many family businesses do not make it through the first succession.Looking at the leaders, this study looks into the difference between family businesses that make it to the next generation and those that do not.Using multiple case studies, this study reveals that attitude toward conflict and benevolence boost confidence in succession process, which increases the likelihood of completing succession.